1997
DOI: 10.1523/jneurosci.17-13-04976.1997
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific and Sensory Neuron-Dependent Increases in Postsynaptic Glutamate Sensitivity Accompany Serotonin-Induced Long-Term Facilitation atAplysiaSensorimotor Synapses

Abstract: Long-term changes in the efficacy of Aplysia sensory neuron (SN) connections accompany behavioral training or applications with 5-HT. The changes evoked by training or 5-HT include formation of new SN varicosities and transmitter release sites. Because new synapse formation requires proper alignment of presynaptic structures with postsynaptic zones containing a high density of transmitter receptors, we examined whether changes in postsynaptic sensitivity to the presumed SN transmitter (glutamate) were correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 70 publications
7
38
1
Order By: Relevance
“…Such transmitters and neuropeptides are known to function during development, where they can regulate neuronal survival, differentiation and maturation, [108][109][110] as well as synaptic plasticity. 111,112 Taken together, we suggest that these data support a model in which cognitive and emotional impairments of schizophrenic patients are caused by two fundamental alterations; persistent qualitative (structural/phenotypic) neural changes that occurred during development, and impaired synaptic plasticity caused by quantitative and qualitative changes in neurotransmitter systems. Both sets of changes can be mediated by altered cytokines and growth factors, interacting with environmental influences.…”
Section: Perspectivessupporting
confidence: 61%
“…Such transmitters and neuropeptides are known to function during development, where they can regulate neuronal survival, differentiation and maturation, [108][109][110] as well as synaptic plasticity. 111,112 Taken together, we suggest that these data support a model in which cognitive and emotional impairments of schizophrenic patients are caused by two fundamental alterations; persistent qualitative (structural/phenotypic) neural changes that occurred during development, and impaired synaptic plasticity caused by quantitative and qualitative changes in neurotransmitter systems. Both sets of changes can be mediated by altered cytokines and growth factors, interacting with environmental influences.…”
Section: Perspectivessupporting
confidence: 61%
“…Possibly, the sensitivity to DNQX of glutamate receptors in solitary motor neurons differs from that of postsynaptic glutamate receptors in sensorimotor co-cultures. This idea receives support from a recent study by Zhu et al (1997). These investigators found a difference in the ability of glutamate receptors in Aplysia motor neurons to undergo a 5-HT-induced increase in sensitivity that depended upon whether or not the glutamate receptors were opposed, or near to, presynaptic varicosities.…”
Section: Discussionmentioning
confidence: 81%
“…Axonal growth, varicosity formation, and increases in synaptic efficacy are all blocked when the actions of sensorin are blocked by exogenous anti-sensorin Ab. Previous studies (Glanzman et al, 1989(Glanzman et al, , 1990Bailey et al, 1992;Bank and Schacher, 1992;Zhu et al, 1997;Casadio et al, 1999;Hatada et al, 1999;Kim et al, 2003) indicate that the formation of varicosities on the major processes of L7 is a consequence of neuritic growth, includes the formation of new release sites, and increases in synaptic efficacy. However, modulation of sensorin levels has little influence on axon extension by sensory neurons growing alone.…”
Section: Sensorin Secretion Regulates Synapse Formation and Maturationmentioning
confidence: 99%